2022
DOI: 10.1038/s10038-022-01100-6
|View full text |Cite|
|
Sign up to set email alerts
|

Expectations, concerns, and attitudes regarding whole-genome sequencing studies: a survey of cancer patients, families, and the public in Japan

Abstract: Whole-genome sequencing (WGS) is being used in research and clinical settings in cancer genomics. Studies show that cancer patients generally have positive attitudes toward tumor profiling tests; however, few works revealed their attitudes toward WGS. This study clarifies the expectations, concerns, and result preferences of cancer patients (CPs), family members (FMs) and general adults (GAs) regarding WGS study in Japan. We conducted an anonymous survey with 1204 CPs, 5968 FMs, and 2915 GAs in 2021. Despite l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Still, another study by Hishiyama et al (2019) reported that 45% of the respondents knew the term genetic information . Our fourth finding is that awareness of another term that has been increasingly incorporated into GR— whole-genome sequencing ( WGS )—seemed to be relatively low among the respondents (29%, the sum of know about it and have heard of it ), but recognition of the WGS study was relatively higher for the patient (43%) and family members of the patient (39%) category groups ( Ri et al, 2022 ).…”
Section: Awareness Attitude and Intentionmentioning
confidence: 87%
See 3 more Smart Citations
“…Still, another study by Hishiyama et al (2019) reported that 45% of the respondents knew the term genetic information . Our fourth finding is that awareness of another term that has been increasingly incorporated into GR— whole-genome sequencing ( WGS )—seemed to be relatively low among the respondents (29%, the sum of know about it and have heard of it ), but recognition of the WGS study was relatively higher for the patient (43%) and family members of the patient (39%) category groups ( Ri et al, 2022 ).…”
Section: Awareness Attitude and Intentionmentioning
confidence: 87%
“…Six of the eight surveys included a certain aspect of GF ( Middleton et al, 2020 ) and GL as components of awareness ( Ikeda, 2008 ; Ishiyama et al, 2008 ; Hishiyama et al, 2019 ; Ri et al, 2022 ; Muto et al, 2023 ). Regarding GF, Middleton et al (2020) reported that 88% of Japanese respondents answered not familiar with DNA, genetics, or genomics .…”
Section: Awareness Attitude and Intentionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even as the associated cost decreases, the infrastructure required for clinical tumor WGS analysis and reporting does not yet exist. As such, many WGS-based classifiers are derived from small datasets across limited cancer types, likely not representative of true cancer type frequencies seen in larger patient populations, and therefore rendering a significant proportion of cancer patients unpredictable within the context of the model [14][15][16] . The expected performance of these models on excluded cancer types (i.e.…”
Section: Introductionmentioning
confidence: 99%